Muddy Paws : Magic Puppy #2 - Bentley, Sue, 1951-; Swan, Angela (New York : Grosset & Dunlap, 2009)
When Beth spends two weeks at her aunt's farm over the summer, her encounter with a magic puppy helps her make friends with her annoying cousin.
Keywords: Dogs -- Fiction; Farm life -- Fiction; Cousins -- Fiction; Magic -- Fiction; Dogs -- Fiction; Farm life -- Fiction; Cousins -- Fiction; Magic -- Fiction